Positive electrode for all-solid-state battery and all-solid-state battery comprising same
By adding porous carbon additives with moderate particle size to the positive electrode active material layer of the all-solid state battery, the problem of high positive electrode porosity is solved, the energy density is improved and the conductivity is maintained, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202480004003.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-21
- Filing Date
- 2024-07-05
- Publication Date
- 2025-04-25
AI Technical Summary
When manufacturing the positive electrode of all solid state batteries, it is necessary to reduce the porosity of the positive electrode of the sulfide-based all solid state battery to improve the energy density and safety of the battery.
By adding porous carbon additives to the positive electrode active material layer, the particle size is between the positive electrode active material and the sulfide-based solid electrolyte, and its specific surface area is controlled to be less than 100m2/g to fill the gap between the positive electrode active material particles and the sulfide-based solid electrolyte particles to reduce the porosity.
It effectively reduces the porosity of the positive electrode, improves the energy density of the all-solid-state battery, maintains conductivity, and improves the overall performance of the battery.
Smart Images

Figure CN119895624A_ABST
Abstract
Description
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2023-0094993, filed on Jul. 21, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] One aspect of the present disclosure relates to a positive electrode for an all-solid-state battery and an all-solid-state battery including the positive electrode. Background Art
[0003] In order to overcome the current limitations of lithium secondary batteries in terms of capacity, safety, output, upsizing, and miniaturization, various batteries are being studied.
[0004] Representative examples include: metal-air batteries with very high theoretical capacity compared to lithium secondary batteries; all-solid-state batteries that are safe and have no risk of explosion; supercapacitors in terms of output power; NaS batteries or redox flow batteries (RFBs) for large-scale applications, and miniaturized thin-film batteries. Academia and industry are conducting continuous research on these technologies.
[0005] All-solid-state batteries refer to batteries that replace the liquid electrolyte used in conventional lithium secondary batteries with solid electrolytes. Since no flammable solvents are used in the battery, there is no possibility of fire or explosion due to decomposition reactions of conventional electrolytes, which significantly improves safety. In addition, among all-solid-state batteries, the development of sulfide all-solid-state batteries is still ongoing. The ionic conductivity of its solid electrolyte is high, and theoretically, it can achieve a high energy density of at least 900Wh / L. Sulfide all-solid-state batteries refer to all-solid-state batteries containing sulfide solid electrolytes.
[0006] In an all-solid-state battery system, lithium ions are not conducted by the liquid electrolyte contained in a conventional lithium-ion battery (LIB). Therefore, when manufacturing the positive electrode of a sulfide-based all-solid-state battery, it is necessary to add small-diameter sulfide-based solid electrolyte particles inside the positive electrode to increase the contact interface between the positive electrode active material and the sulfide-based solid electrolyte particles, thereby improving lithium ion conductivity. In addition, in order to improve energy density, the physical contact between the positive electrode active material, the sulfide-based solid electrolyte particles, and other battery components in the positive electrode must be enhanced, and the porosity of the positive electrode must be reduced after rolling, and this state must be maintained during charging and discharging.
[0007] Therefore, it is necessary to develop technologies to further reduce the porosity of sulfide-based all-solid-state battery cathodes to improve the performance of all-solid-state batteries.
[0008] [Prior art literature]
[0009] [Patent Document]
[0010] (Patent Document 1)
[0011] Korean Patent Publication No. 2016-0118597 Summary of the invention
[0012] [Technical issues]
[0013] The inventors of the present invention have conducted extensive research to solve the above-mentioned problems, and have found that when manufacturing a positive electrode active material layer for a positive electrode for an all-solid-state battery, wherein a positive electrode active material, a sulfide solid electrolyte, a conductive material and a porous carbon additive are used, and the particle size of the porous carbon additive is between the particle size of the positive electrode active material and the particle size of the sulfide solid electrolyte to fill the gaps between the positive electrode active material particles and the sulfide solid electrolyte particles, if the specific surface area of the porous carbon additive is limited to below a certain level, the porosity of the positive electrode active material layer is reduced and the energy density of the all-solid-state battery is improved.
[0014] Therefore, an object of the present disclosure is to provide a positive electrode for an all-solid-state battery having reduced porosity.
[0015] Another object of the present disclosure is to provide an all-solid-state battery including a positive electrode for an all-solid-state battery having reduced porosity.
[0016] [Technical solution]
[0017] In order to achieve the above object, the present invention provides a positive electrode for an all-solid-state battery, which comprises a positive electrode active material, a sulfide solid electrolyte, a conductive material and a porous carbon additive.
[0018] The particle size of the porous carbon additive is between the particle size of the positive electrode active material and the particle size of the sulfide solid electrolyte.
[0019] The porous carbon additive has a BET specific surface area of 100 m 2 / g or less low specific surface area porous carbon additive.
[0020] The present invention also provides a positive electrode for an all-solid-state battery, wherein the BET specific surface area of the porous additive is 70 m 2 / g or less.
[0021] The present invention also provides a positive electrode for an all-solid-state battery, wherein the particle size (D50) of the porous carbon additive is 1.0 μm to 4.0 μm.
[0022] The present invention also provides a positive electrode for an all-solid-state battery, wherein the stacking density of the porous carbon additive is greater than 0.18 g / cc.
[0023] The present invention also provides a positive electrode for an all-solid-state battery, wherein the powder resistivity of the porous carbon additive is less than 0.05 ohm·cm.
[0024] The present invention also provides a positive electrode for an all-solid-state battery, wherein the particle size (D50) of the positive electrode active material is 3.0 μm to 8.0 μm.
[0025] The present invention also provides a positive electrode for an all-solid-state battery, wherein the particle size (D50) of the sulfide solid electrolyte is 0.1 μm to 1.5 μm.
[0026] The present disclosure also provides a positive electrode for an all-solid-state battery, wherein the positive electrode is in the form of a pellet comprising a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a porous carbon additive.
[0027] The present invention also provides a positive electrode for an all-solid-state battery, which comprises: a positive electrode current collector and a positive electrode active material layer formed on one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a sulfide solid electrolyte, a conductive material, an adhesive and a porous carbon additive.
[0028] The present invention also provides a positive electrode for an all-solid-state battery, wherein the binder includes one or more selected from the group consisting of: polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenol resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride-co-hexafluoropropylene).
[0029] The present invention also provides a positive electrode for an all-solid-state battery, wherein the conductive material is at least one linear conductive material selected from the group consisting of carbon nanotubes (CNTs) and carbon nanofibers (CNFs).
[0030] The present invention also provides a positive electrode for an all-solid-state battery, wherein the porous carbon additive is one or more selected from the group consisting of soft carbon and hard carbon.
[0031] The present invention also provides a positive electrode for an all-solid-state battery, wherein the porous carbon additive is one or more selected from the group consisting of activated carbon and carbon black.
[0032] The present invention also provides a positive electrode for an all-solid-state battery, wherein the porosity of the positive electrode is 5 volume % to 19 volume %.
[0033] The present disclosure also provides a positive electrode for an all-solid-state battery, wherein the content of the positive electrode active material is 55 weight % to 90 weight % based on the total weight of the positive electrode; wherein the content of the sulfide solid electrolyte is 10 weight % to 50 weight % based on the total weight of the positive electrode; wherein the content of the conductive material is 0.05 weight % to 10 weight % based on the total weight of the positive electrode; wherein the content of the porous carbon additive is 0.1 weight % to 3 weight % based on the total weight of the positive electrode.
[0034] The present disclosure also provides an all-solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte membrane disposed between the positive electrode and the negative electrode.
[0035] [Beneficial Effects]
[0036] According to the positive electrode for an all-solid-state battery of the present invention, the porous carbon additive can reduce the porosity of the positive electrode by filling the gaps between the positive electrode active material particles and the sulfide solid electrolyte, thereby improving the energy density of the all-solid-state battery. In addition, by using a linear conductive material as a conductive material for the positive electrode of the all-solid-state battery, the conductivity of the positive electrode is maintained, so that the effect of improving the energy density can be achieved without reducing the performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a scanning electron microscope photograph of the positive electrode side of the mixture prepared in Example 2, Comparative Example 3, and Comparative Example 4. DETAILED DESCRIPTION
[0038] Hereinafter, the present disclosure will be described in more detail to provide a better understanding.
[0039] The terms and words used in this specification and claims should not be interpreted by their ordinary meanings or dictionary meanings, but should be interpreted based on the principle that the inventor can appropriately define the concepts of the terms to best describe his / her invention, with the meanings and concepts consistent with the technical ideas of the present invention.
[0040] In this specification, in order to classify positive electrodes manufactured using a binder and not using a binder in a positive electrode active material layer, the one without a binder may be referred to as a "composite positive electrode" and the one with a binder may be referred to as a "positive electrode".
[0041] Positive electrode for all-solid-state battery
[0042] The present disclosure relates to a positive electrode for an all-solid-state battery.
[0043] The positive electrode for an all-solid-state battery disclosed herein comprises a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a porous carbon additive.
[0044] In one example of the present disclosure, the positive electrode may be in the form of a pressed sheet. The pressed sheet-like positive electrode may be used in the form of a current collector-free, or the pressed sheet may be placed on top of the current collector to form the positive electrode. The pressed sheet may be formed by pressing a composite powder comprising a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a porous carbon additive. Since the pressed sheet may not contain a binder, any resistance that may be caused by the binder is eliminated.
[0045] In another example of the present disclosure, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on one side of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, a binder, and a porous carbon additive.
[0046] The particle size of the porous carbon additive is between that of the positive electrode active material and that of the sulfide solid electrolyte. The BET specific surface area of the porous carbon additive can be 100 m 2 / g or less. Considering the specific surface area, the conductive material may be a linear conductive material. As used herein, a positive electrode without a binder may correspond to a composite positive electrode.
[0047] In the positive electrode for the all-solid-state battery of the present invention, due to the different particle sizes of the positive electrode active material particles and the sulfide solid electrolyte particles, voids are formed, and the porous carbon additive is used to fill these voids, thereby reducing the porosity of the positive electrode and improving the energy density. Since the particle size (D50) of the porous carbon additive is larger than the particle size (D50) of the sulfide solid electrolyte and smaller than the particle size (D50) of the positive electrode active material, the voids can be filled with the porous carbon additive.
[0048] In one example of the present disclosure, the BET specific surface area of the porous carbon additive may be 100 m 2 Specifically, the BET specific surface area of the porous carbon additive can be 100 m 2 / g or less, 90m 2 / g or less, 80m 2 / g or less, 70m 2 / g or less, 60m 2 / g or less, 50m 2 / g or less, 40m 2 / g or less, or 30m 2 / g or less. If the BET specific surface area is greater than 100m 2 / g, the contact interface between the high specific surface area porous carbon additive and the sulfide-based all-solid electrolyte used for the positive electrode can be increased, which can increase the electrolyte degradation reaction and reduce the ionic conductivity of the positive electrode itself. In addition, the lower limit of the BET specific surface area is not particularly limited, but can be 5m 2 / g or above.
[0049] The porous carbon additive has a low specific surface area as defined above and may be referred to as macroporous carbon.
[0050] In addition, the particle size (D50) of the porous carbon additive may be 1.0 μm to 4.0 μm. Specifically, the particle size (D50) of the porous carbon additive may be greater than 1.0 μm, greater than 1.5 μm, or greater than 2.0 μm, and may be less than 3.0 μm, less than 3.5 μm, or less than 4.0 μm. If the particle size (D50) of the porous carbon additive is less than 1.0 μm, the particles are too small to fill the voids formed by the particle size difference between the positive electrode active material particles and the sulfide solid electrolyte particles, and the porous carbon additive may only be adsorbed on the surface of the positive electrode active material; if it is greater than 4.0 μm, it is difficult to fill the voids formed by the particle size difference between the positive electrode active material particles and the sulfide solid electrolyte particles, so the effect of reducing the porosity of the positive electrode may not be significant.
[0051] The particle size (D50) can be measured by introducing the porous carbon additive into a particle size analyzer (Mastersizer 3000, Malvern).
[0052] Furthermore, the bulk density of the porous carbon additive may be greater than 0.18 g / cc.
[0053] Specifically, the bulk density may be greater than or equal to 0.18 g / cc, greater than or equal to 0.19 g / cc, or greater than or equal to 0.20 g / cc. If the bulk density is less than 0.18 g / cc, the porous carbon additive itself may have a lower density, thereby reducing the overall density of the positive electrode. The upper limit of the bulk density is not particularly limited, but may be less than 0.5 g / cc.
[0054] Bulk density can be measured using a densitometer conforming to ASTM D 1895.
[0055] The powder resistivity of the porous carbon additive may be 0.05 ohm·cm or less.
[0056] Specifically, the powder resistivity may be less than 0.05 ohm·cm, less than 0.04 ohm·cm, or less than 0.03 ohm·cm. If the powder resistivity is greater than 0.05 ohm·cm, when the content of the porous carbon additive in the positive electrode exceeds a certain proportion, the overall resistance of the positive electrode may increase. The lower limit of the powder resistivity is not particularly limited, but may be greater than or equal to 0.005 ohm·cm. If the powder resistivity becomes too small, the electron transfer of the sulfide-based all-solid electrolyte in contact with the porous carbon additive may be active, causing the sulfide-based all-solid electrolyte to exhibit a decomposition reaction.
[0057] The powder resistance can be measured using a powder resistivity meter (HPRM-FA2, Hantech). The lower punch is mounted on the main body of the powder resistivity meter die, and then a sample of a known weight for measuring a conductive material is weighed, and the upper punch is mounted and placed in the powder resistivity meter. The powder resistivity meter is then run, from 0kgf to 2000kgf with an increment of 400kgf, and the final powder resistivity at 2000kgf (196MPa) can be observed.
[0058] In addition, the porous carbon additive may include one or more selected from the group consisting of soft carbon and hard carbon, but is not limited thereto as long as it is a carbon material in particle form. For example, the porous carbon additive may be one or more selected from the group consisting of activated carbon and carbon black.
[0059] In addition, based on the total weight of the positive electrode active material layer, the content of the porous carbon additive may be 0.1 to 3 weight %. Specifically, the content of the porous carbon additive may be 0.1 weight %, 0.2 weight % or more, 0.3 weight % or more, 0.4 weight % or more, or 0.5 weight % or more, 1.2 weight % or less, 1.5 weight % or less, 2.0 weight % or less, 2.5 weight % or less, or 3.0 weight % or less. If the content of the porous carbon additive is less than 0.1 weight %, the energy density improvement effect brought about by the reduced porosity using the porous carbon additive may not be significant; if the content is greater than 3 weight %, the mass transfer resistance may be greater.
[0060] In one example of the present disclosure, the particle size (D50) of the positive active material may be 3.0 μm to 8.0 μm.
[0061] Specifically, the particle size (D50) of the positive electrode active material may be 3.0 μm or more, 3.5 μm or more, or 4.0 μm or more, and may be 6.0 μm or less, 6.5 μm or less, 7.0 μm or less, 7.5 μm or less, or 8.0 μm or less. If the particle size (D50) of the positive electrode active material is less than 3.0 μm, even if the positive electrode active material and the all-solid electrolyte are dispersed in the same weight ratio, the dispersion may be reduced due to the small particle size of the positive electrode active material; if it is greater than 7.0 μm, excessive voids may be formed in the positive electrode active material layer, thereby possibly reducing the performance of the all-solid-state battery.
[0062] The particle size (D50) can be measured by introducing the positive electrode active material into a particle size analyzer (Mastersizer 3000, Malvern).
[0063] In addition, the positive electrode active material can be any material that can reversibly absorb and release lithium ions, and is not particularly limited thereto, for example: layered compounds such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga and In; 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1, x+y+z+v=1), Li(Li a M b-a-b' M' b' ) 2-c A c (wherein, 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2 and 0≤c≤0.2; M comprises one or more selected from the group consisting of Mn, Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' comprises one or more selected from the group consisting of Al, Mg and B; A comprises one or more selected from the group consisting of P, F, S and N), or a compound substituted by one or more transition metals; lithium manganese compounds, such as Li 1+y Mn 2-y O4 (wherein y is 0 to 0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, LiFe3O4, V2O5 or Cu2V2O7; 1-y M y Ni-type lithium nickel oxide represented by O2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); 2-y M yO2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li is replaced by alkaline earth metal ions; disulfide; Fe2(MoO4)3; etc., but not limited to these.
[0064] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 55 wt % to 90 wt %. Specifically, the content of the positive electrode active material may be 55 wt %, 60 wt % or more, or 65 wt % or more, 83 wt % or less, 85 wt % or less, or 90 wt % or less. If the content of the positive electrode active material is less than 55 wt %, the battery performance may be reduced, and if the content is greater than 90 wt %, the mass transfer resistance may be increased.
[0065] In one example of the present disclosure, the particle size (D50) of the sulfide-based solid electrolyte may be 0.1 μm to 1.5 μm.
[0066] Specifically, the particle size (D50) of the sulfide solid electrolyte may be 0.1 μm or more, 0.3 μm or more, or 0.5 μm or more, and may be 0.9 μm or less, 1.0 μm or less, 1.2 μm or less, or 1.5 μm or less. If the particle size (D50) of the sulfide solid electrolyte is less than 0.1 μm, the ultrafine all-solid electrolyte cannot be fully dispersed in the positive electrode layer and agglomeration may occur, and if it is greater than 1.5 μm, the dispersion may be slightly easier, but the contact surface with the positive electrode active material particles may be reduced, and the positive electrode porosity may increase.
[0067] In addition, the sulfide-based solid electrolyte may include one or more selected from the group consisting of LiPSX (wherein X is Cl, Br or I), LiGePS and LiPS. However, the sulfide-based solid electrolyte is not limited to these, and a wide range of sulfide-based solid electrolytes conventionally used in the art can be used.
[0068] In addition, based on the total weight of the positive electrode active material layer, the content of the sulfide solid electrolyte may be 10 wt % to 50 wt %. Specifically, the content of the sulfide solid electrolyte may be 10 wt % or more, 20 wt % or more, or 30 wt % or more, and may be 40 wt % or less, 45 wt % or less, or 50 wt % or less. If the content of the positive electrode active material is less than 10 wt %, it is insufficient to fill the voids formed in the positive electrode active material layer, thereby making it difficult to reduce the porosity of the positive electrode active material. If it is greater than 50 wt %, the content of the positive electrode active material and the conductive material may be relatively reduced, resulting in a decrease in battery performance.
[0069] In one example of the present disclosure, the conductive material may be a linear conductive material, wherein the linear conductive material may be one or more selected from carbon nanotubes (CNTs) and carbon nanofibers (CNFs). The linear conductive material may improve conductivity due to its morphological characteristics.
[0070] In addition, based on the total weight of the positive electrode active material layer, the content of the conductive material may be 0.05 wt % to 10 wt %. Specifically, the content of the conductive material may be 0.05 wt % or more, 0.1 wt % or more, 0.5 wt % or more, 1 wt % or more, 2 wt % or more, or 3 wt % or more, and may be 5 wt % or less, 7 wt % or less, or 10 wt % or less. If the content of the conductive material is less than 0.05 wt %, the conductivity of the positive electrode may deteriorate, and if it is greater than 10 wt %, the content of the positive electrode active material and the sulfide solid electrolyte may be relatively reduced, resulting in degradation of battery performance.
[0071] In one example of the present disclosure, the positive electrode active material layer may further include a binder. The binder may be included to promote bonding between materials contained in the positive electrode active material layer and bonding between the positive electrode active material layer and the positive electrode current collector. The binder may further reduce the positive electrode porosity by promoting bonding between materials contained in the positive electrode active material layer.
[0072] The binder may be a fibrous binder. Due to fiberization during mixing during the manufacture of the positive electrode, the binder may be incorporated into the positive electrode active material layer in the form of fibers. Therefore, in terms of its physical properties, it is preferred that the binder is easily deformable.
[0073] The binder may include one or more selected from the group consisting of polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenol resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly (vinylidene fluoride-co-hexafluoropropylene). Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0074] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 0.1% by weight to 3% by weight. Specifically, the content of the binder may be 0.1% by weight or more, 0.5% by weight or more, 0.8% by weight or more, or may be 1.5% by weight or less, 2% by weight or less, or 3% by weight or less. If the content of the binder is less than 0.1% by weight, the effect of improving the cohesion of the material contained in the positive electrode active material layer may be small, and the electrode sheet may not be properly formed, and if the content is greater than 3% by weight, the ionic conductivity or conductivity may be reduced.
[0075] In one example of the present disclosure, the porosity of the positive electrode active material layer may be 5 volume % to 19 volume %.
[0076] Specifically, the porosity may be 5% by volume or more, 8% by volume or more, 10% by volume or more, or 13% by volume or more, and may be 17% by volume or less, 18% by volume or less, or 19% by volume or less. The porosity is within a range optimized by considering performance such as the energy density of the battery, and if the porosity is greater than 19% by volume, the energy density of the battery may be reduced.
[0077] In one example of the present disclosure, the thickness of the positive electrode active material layer may be 100 μm to 300 μm, more specifically, 100 μm or more, 110 μm or more, 120 μm or more, 200 μm or less, 250 μm or less, or 300 μm or less. However, the thickness of the positive electrode active material layer is not limited thereto, and the thickness may be adjusted to have a suitable positive electrode loading according to the performance improvement of various positive electrode components contained in the positive electrode active material layer.
[0078] In one example of the present disclosure, the positive electrode current collector supports the positive electrode active material layer and serves to transfer electrons between an external wire and the positive electrode active material layer.
[0079] There is no particular limitation on the positive electrode current collector, as long as it has high electronic conductivity and does not cause chemical changes in the all-solid-state battery. For example, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, stainless steel whose surface is treated with carbon, nickel or silver, aluminum-cadmium alloy, etc., can be used as the positive electrode current collector.
[0080] The positive electrode current collector may have a microscopic uneven structure or a three-dimensional porous structure on the surface of the positive electrode current collector to strengthen the bonding force with the positive electrode active material layer. Therefore, the positive electrode current collector may include various forms, such as films, sheets, foils, screens, nets, porous materials, foams, non-woven fabrics, etc.
[0081] Method for preparing positive electrode for all-solid-state battery
[0082] The present disclosure relates to a method for manufacturing a positive electrode for an all-solid-state battery. The specific materials, properties and contents of the positive electrode active material, sulfide solid electrolyte, conductive material, porous carbon additive and binder used in the preparation method of the positive electrode for an all-solid-state battery of the present invention are as described above.
[0083] In the present disclosure, a positive electrode may be classified as a "composite positive electrode" without a binder or a "positive electrode" with a binder.
[0084] In one example of the present disclosure, a method for preparing a composite positive electrode without a binder may include: (A1) mixing a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a porous carbon additive; and (A2) forming the mixed powder obtained in step (A1) into a tablet form. The tablet form in step (A2) may be formed by pressing with a fixture.
[0085] The composite cathode prepared as described above can be applied to a pressure fixture battery cell. Since the composite cathode does not contain a binder, the bonding factor as a resistance factor can be eliminated. Therefore, the composite cathode can be used in a pressure fixture battery cell for performance evaluation while eliminating the resistance factor.
[0086] In addition, in one example of the present disclosure, a method for manufacturing a positive electrode containing a binder includes: (B1) mixing a positive electrode active material, a sulfide solid electrolyte, a conductive material, a porous carbon additive and a binder; (B2) applying the mixed powder obtained in step (B1) to a calendering process to form a film; and (B3) attaching the film layer of the positive electrode active material obtained in step (B2) to the positive electrode current collector.
[0087] The mixing in step (B1) can be physical mixing, wherein the binder can be fibrillated by physical mixing. During physical mixing, the binder can be physically deformed by friction with the particles in the mixed powder by shear force, thereby causing fibrillation. For example, PTFE with a physical property that is easily deformed can be used as a binder. In addition, physical deformation can be achieved by introducing induction, ball milling or roller pressing during mixing.
[0088] Furthermore, in step (B2), the mixed powder obtained in step (B1) may be subjected to a calendering process to be molded into a film.
[0089] The conditions of the calendering process may be to apply appropriately controlled process conditions for film formation. For example, the calendering process may be performed at a temperature of 50° C. to 200° C. for 5 to 50 cycles. However, the calendering process conditions (such as temperature pressure or number of cycles) may be any of those used in the electrode manufacturing process used in the conventional battery field.
[0090] Furthermore, in step (B3), the film-formed cathode active material layer obtained in step (B2) is attached to a cathode current collector to prepare a cathode for an all-solid-state battery.
[0091] All-solid-state battery
[0092] The present disclosure relates to an all-solid-state battery including a solid electrolyte membrane.
[0093] The all-solid-state battery disclosed herein comprises a positive electrode, a negative electrode and a sulfide-based solid electrolyte layer disposed therebetween. The positive electrode is as described above.
[0094] In one example of the present invention, the negative electrode includes a negative electrode active material layer, wherein the negative electrode active material layer may be formed on one side of a negative electrode current collector.
[0095] The negative electrode active material layer may include a negative electrode active material, a conductive material, and a binder. Alternatively, the negative electrode active material layer may be an anode-free layer.
[0096] In the negative electrode active material layer, the negative electrode active material may include a + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.
[0097] Able to reversibly insert or remove lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0098] Preferably, the negative electrode active material may be lithium metal or lithium-indium alloy (Li-In), and more specifically, it may be in the form of lithium metal or lithium thin film or lithium-indium alloy thin film or powder.
[0099] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material may be 40% to 80% by weight. Specifically, the content of the negative electrode active material may be 40% by weight or more, 50% by weight or more, or may be 70% by weight or less, or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the connectivity between the wet negative electrode active layer and the dry negative electrode active layer may be insufficient, and if the content is greater than 80% by weight, the mass transfer resistance may increase.
[0100] The binder is a component that helps the negative electrode active material to adhere to the conductive material or to the negative electrode current collector, and may include one or more selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol , polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly (vinylidene fluoride-co-hexafluoropropylene). Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0101] In addition, based on the total weight of the negative electrode active material layer, the content of the binder may be 0.5% by weight to 4% by weight, more specifically, the content of the binder may be 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 3% by weight or less, 3.5% by weight or less, or 4% by weight or less. If the binder content is less than 0.5% by weight, the adhesion of the positive electrode active material to the negative electrode current collector may be reduced, and if the binder content is greater than 4% by weight, the adhesion may be improved, but the content of the negative electrode active material may be reduced, resulting in a lower cell capacity.
[0102] In addition, the conductive material is not particularly limited, as long as it prevents side reactions in the internal environment of the all-solid-state battery and has excellent conductivity without causing chemical changes in the battery, and graphite or conductive carbon can be used as a representative, for example, graphite, such as natural graphite, artificial graphite, etc.; carbon black, such as carbon black, acetylene black, Ketjen black, denka black, thermal black, channel black, furnace black, lamp black and summer black, etc.; carbon materials having a graphene or graphite crystal structure; conductive fibers, such as carbon fibers, metal fibers, etc.; carbon fluoride; metal powders, such as aluminum powder, nickel powder, etc.; conductive whiskers, such as zinc oxide, potassium titanate, etc.; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; the above materials can be used alone or in the form of a mixture of two or more, but are not necessarily limited thereto. Preferably, the conductive material may include vapor grown carbon fibers (VGCF).
[0103] In addition, based on the total weight of the negative electrode active material layer, the content of the conductive material may be 1 wt % to 5 wt %, more specifically, the content of the conductive material may be 1 wt % or more, 1.5 wt % or more, 2 wt % or more, 4 wt % or less, 4.5 wt % or less, or 5 wt % or less. If the content of the conductive material is too low, for example, less than 1 wt %, it is difficult to expect the effect of improving the conductivity, or the electrochemical performance of the battery may deteriorate, and if the content is too high, for example, more than 5 wt %, the content of the negative electrode active material may be relatively low, resulting in reduced capacity and energy density. There is no substantial limitation on the method of incorporating the conductive material into the negative electrode, and any conventional method known in the art may be used, such as mixing with the negative electrode active material or coating the negative electrode active material.
[0104] In addition, the negative electrode current collector is not particularly limited as long as it is conductive and does not cause chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel treated with carbon, nickel or silver on the surface, aluminum-cadmium alloy, etc. can be used. In addition, similar to the positive electrode current collector, the negative electrode current collector can take various forms, for example, a film, sheet, foil, net, porous material, foam, non-woven fabric, etc., with fine concavoconvexity formed on the surface.
[0105] The manufacturing method of the negative electrode is not particularly limited, and can be manufactured by forming a negative electrode active material layer on the negative electrode current collector using a conventional method for forming a layer or film. For example, methods such as pressing, coating or deposition can be used. The negative electrode of the present invention also includes the following: there is no lithium film on the negative electrode current collector, and a metal lithium film is formed on the metal plate by initial charging after the battery is assembled.
[0106] In addition, the anode-free layer refers to a negative electrode layer in which lithium metal or lithium alloy that can serve as a lithium source does not exist in the negative electrode active material during initial assembly of the battery, but lithium is precipitated in the negative electrode by charging. A battery including the anode-free layer may be referred to as an anode-free battery.
[0107] In an anode-free battery, during the battery charge and discharge process, lithium ions released from the positive electrode migrate to the negative electrode to form a negative electrode active material layer. For example, during battery charging, lithium ions are released from the positive electrode active material and migrate to the negative electrode side to form lithium metal composed only of lithium, to form a lithium metal layer on the negative electrode current collector, or to form any other form of lithium metal structure other than a layer form. Any other form may refer to a structure in which lithium metal is aggregated in the form of particles, for example.
[0108] In one example of the present disclosure, the sulfide solid electrolyte contained in the sulfide solid electrolyte layer may include one or more selected from the group consisting of LiPSX (wherein X is Cl, Br or I), LiGePS and LiPS. However, the sulfide solid electrolyte is not limited to these, and a wide range of sulfide solid electrolytes conventionally used in the art can be used.
[0109] Battery Module
[0110] The present disclosure also relates to a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0111] Specific examples of such devices include, but are not limited to: power tools powered by motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems, etc.
[0112] Example
[0113] Hereinafter, for the purpose of illustrating the present disclosure, preferred embodiments of the present disclosure are described, but it will be apparent to those skilled in the art that various changes and modifications may be made within the scope and technical concept of the present disclosure, and such changes and modifications fall within the scope of the appended patent claims.
[0114] In the following examples and comparative examples, a positive electrode and an all-solid-state battery including the positive electrode were prepared according to the composition of the positive electrode active material layer and the properties of the raw materials described in Table 1 below.
[0115] [Table 1]
[0116]
[0117] Example 1: Preparation of composite positive electrode
[0118] The positive electrode was prepared as follows: LiN 0.8 Co 0.1 Mn 0.1 O2 (NCM811) was used as the positive electrode active material, Li6PS5Cl was used as the sulfide solid electrolyte, carbon nanofibers (CNF) were used as the linear conductive material, and porous carbon additives (Heraeus, BET≤60m 2 / g) is used as an additive. Hereinafter, this porous carbon additive is referred to as a low specific surface area porous carbon additive 1.
[0119] The positive electrode active material, sulfide solid electrolyte, conductive material and porous carbon additive were powder mixed at a weight ratio of 60:35:4:1. Specifically, the positive electrode active material and the sulfide solid electrolyte were quantitatively added in a powder state and mixed for 15 minutes using an agate mortar in a dry room environment to obtain a mixture. The conductive material and the porous additive were then quantitatively added to the above mixture and then mixed for another 15 minutes to obtain a mixed powder.
[0120] The mixed powder was pressurized using a pressurizing fixture and prepared to 3 mAh / cm 2 Loaded pressed composite positive electrode.
[0121] Example 2: Preparation of positive electrode
[0122] The positive electrode was prepared as follows: LiN 0.8 Co 0.1 Mn 0.1 O2 (NCM811) was used as the positive electrode active material, Li6PS5Cl was used as the sulfide solid electrolyte, carbon nanofiber (CNF) was used as the linear conductive material, and a low specific surface area porous additive 1 (Heraeus, BET≤60m 2 / g) as a porous additive and polytetrafluoroethylene (PTFE) as a binder.
[0123] The positive electrode active material, sulfide solid electrolyte, conductive material, porous carbon additive and binder are powdered and mixed in a weight ratio of 83:15:0.8:0.2:1. Specifically, the positive electrode active material and the sulfide solid electrolyte are quantitatively measured in a powder state and mixed for 15 minutes using a blade mixer in a dry chamber environment to obtain a mixture. The conductive material and the low specific surface area porous carbon additive 1 are then quantitatively measured and then added to the above mixture, and then the binder polytetrafluoroethylene (PTFE) powder is quantitatively measured and then further mixed to obtain a mixed powder.
[0124] After the mixed powder was introduced into a mortar, it was fiberized in the mortar and rolled in a roll press to prepare a positive electrode with a thickness of 150 μm.
[0125] Comparative Example 1
[0126] A composite cathode was prepared in the same manner as in Example 1, except that no porous carbon additive was used.
[0127] Comparative Example 2
[0128] The composite positive electrode was prepared in the same manner as in Example 1, except that a high specific surface area porous carbon additive (Heraeus, BET ≥ 500 m 2 / g) instead of the low specific surface area porous carbon additive 1 as the porous carbon additive.
[0129] Comparative Example 3
[0130] A positive electrode was prepared in the same manner as in Example 2, except that the porous carbon additive was not used.
[0131] Comparative Example 4
[0132] The positive electrode was prepared in the same manner as in Example 2, except that a porous carbon additive (Heraeus, BET ≤ 60 m) having a smaller particle size than the porous carbon additive (low specific surface area porous carbon additive 1) used in Example 2 was used. 2 / g). Hereinafter, the porous carbon additive having a particle size smaller than that of the low specific surface area porous carbon additive 1 is referred to as the low specific surface area porous carbon additive 2.
[0133] Experimental Example 1: Evaluation of All-Solid-State Battery Performance
[0134] The performance evaluation of the all-solid-state battery is performed based on whether the positive electrode active material layer contains a porous carbon additive and the specific surface area of the porous carbon additive. The composite positive electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 were evaluated.
[0135] In order to evaluate the performance of all-solid-state batteries, the pressure fixture cells were prepared by the following method.
[0136] After the pressed sheet composite positive electrode is transferred to the pressure fixture battery cell, the sulfide solid electrolyte powder (200 mg) is placed on the pressed sheet and pressurized with a force of 400 MPa for 60 seconds to form a film-like sulfide solid electrolyte layer. Then, the lithium metal negative electrode is placed on one side of the sulfide solid electrolyte layer, and pressurized again with a force of 100 MPa to increase the contact between the sulfide solid electrolyte layer and the negative electrode. Then, the pressure fixture battery cell is prepared by tightening under appropriate pressure.
[0137] The capacity capability of the press fixture cell was observed by the following scheme: the battery was activated to 0.05C in a charger / discharger for 2 cycles and then discharged to 1C. The results are shown in Tables 2 and 3 below. In particular, the capacity capability was observed by the following scheme: charging at 0.05C CC / CV (constant current / constant voltage), discharging at 0.05C CC (constant current), 2 cycles in a charger / discharger, then charging at 0.1C CC / CV, but discharging at CC of 0.1C / 0.2C / 0.33C / 0.5C / 1C.
[0138] [Table 2]
[0139]
[0140] Referring to Table 2 above, it can be seen that Example 1 and Comparative Example 1 contain and do not contain the low specific surface area porous carbon additive 1, respectively. After two cycles of formation, the discharge capacity performance of Example 1 is better than that of Comparative Example 1. In addition, Example 1 and Comparative Example 2 contain the low specific surface area porous carbon additive 1 and the high specific surface area porous carbon additive 2, respectively. It can be seen that the initial efficiency of Comparative Example 2 is comparable to that of Example 1, but the discharge capacity is slightly worse.
[0141] [Table 3]
[0142]
[0143] With reference to Table 3 above, it can be confirmed that Example 1 has a better discharge capacity retention rate than Comparative Examples 1 and 2. Specifically, Example 1 also maintains a discharge capacity of 185 mAh / g when discharged at 1C, while the discharge capacity measured in Comparative Examples 1 and 2 is less than 170 mAh / g. This is because when the specific surface area of the porous carbon additive in the composite positive electrode is high (Comparative Example 2), the decomposition reaction of the sulfide solid electrolyte in contact with the porous carbon additive is accelerated with the increase of the c-rate. In addition, when the positive electrode does not contain a porous carbon additive (Comparative Example 1), the conductive network is fully formed due to the use of a linear conductive material, but the porosity of the composite positive electrode in the pressure fixture battery cell can be higher than the porosity of the positive electrode with a porous carbon additive, so it can be inferred that the lithium ion conductivity is reduced, resulting in a reduction in the discharge capacity retention rate.
[0144] Experimental Example 2: Confirmation of the internal structure of the positive electrode
[0145] Experiments were conducted to measure whether a porous carbon additive was included in a positive electrode active material layer containing a binder and the effect of the particle size of the porous carbon additive on the internal structure and conductivity of the positive electrode. Example 2, Comparative Example 3 and Comparative Example 4 were evaluated. They all contained a binder in the positive electrode active material layer.
[0146] The positive electrodes prepared in Example 2, Comparative Example 3 and Comparative Example 4 were further pressurized using a hot isostatic press (WIP) to allow the positive electrode components to be fully contacted, and the side of the positive electrode was observed using a scanning electron microscope (SEM). Example 2, Comparative Example 3 and Comparative Example 4 are all examples of using a binder in the positive electrode manufacturing process, wherein Example 2 contains a low specific surface area porous carbon additive 1, Comparative Example 3 does not contain a porous carbon additive, and Comparative Example 4 contains a low specific surface area porous carbon additive 2 having a smaller particle size than Example 2.
[0147] Figure 1 is a scanning electron micrograph of the side surface of the positive electrode prepared using the positive electrode materials in Example 2, Comparative Example 3 and Comparative Example 4.
[0148] Reference Figure 1 , it can be seen that, compared with Comparative Example 3 not containing the porous carbon additive, Example 2 and Comparative Example 4 containing the porous carbon additive did not reduce the dispersibility of the components contained in the positive electrode active material layer.
[0149] In addition, the porosity was measured before and after WIP rolling, and the conductivity was measured using the manufactured positive electrode, and the results are shown in the following Table 4. According to the following formula 1, the porosity was measured using the positive electrode density calculated from: 1) the thickness of the positive electrode after WIP rolling, 2) the weight of the positive electrode, 3) the area of the positive electrode, and 4) the density of the positive electrode component used.
[0150] [Formula 1]
[0151] Porosity of positive electrode (%) = (1-([positive electrode weight] / [positive electrode area × positive electrode thickness]) / [positive electrode component density]) × 100
[0152] In addition, the conductivity (S / cm) was determined by preparing a positive electrode to make an electrode for conductivity measurement, then contacting a conductive Al foil on one side of the positive electrode, and then pressing it with WIP, and then calculating the reciprocal of the resistance value (ohm·cm) obtained by contacting with a multi-probe of an electrode resistance measurement system (RM2610, Hioki), and recording the average value after 3 measurements.
[0153] [Table 4]
[0154] Example 2 Comparative Example 3 Comparative Example 4 Porosity after rolling (vol%) 16 19.2 20.5 Conductivity (S / cm) 5.9.E-05 5.0.E-05 4.7.E-05
[0155] Referring to Table 4 above, compared with before rolling, Example 2 containing the low specific surface area porous carbon additive 1 has a positive electrode porosity reduced by about 3 volume % compared with Comparative Example 3 without the porous carbon additive. In addition, it was found that the conductivity measured using the positive electrode of Example 2 was greater than that of Comparative Examples 3 and 4.
[0156] Compared with the low specific surface area porous carbon additive 1 of Example 2, the positive electrode of Comparative Example 4 including the low specific surface area porous carbon additive 2 having a smaller particle size has an increased porosity after rolling and has the lowest conductivity.
[0157] The particle size of the low specific surface area porous carbon additive 1 (D50, 1.7 μm) used in Example 2 is between the positive electrode active material (D50, 5 μm) and the sulfide solid electrolyte (D50, 0.7 μm). Compared with the low specific surface area porous carbon additive 1 of Example 2, the low specific surface area porous carbon additive 2 used in Comparative Example 4 has a smaller particle size, so it was originally expected that it would more effectively fill the voids formed by the positive electrode active material and the sulfide solid electrolyte, but due to its extremely low particle size and the fine powder obtained therefrom, it was found that it was only adsorbed on the surface of the positive electrode active material without reducing the porosity of the entire positive electrode active material layer.
[0158] Therefore, it can be expected that the low specific surface area porous carbon additive 1 used in Example 2 will reduce the porosity of the positive electrode active material layer, thereby improving the performance of the positive electrode.
Claims
1. A positive electrode for an all-solid-state battery, comprising a positive electrode active material, a sulfide solid electrolyte, a conductive material and a porous carbon additive, in, The particle size of the porous carbon additive is between the particle size of the positive electrode active material and the particle size of the sulfide-based solid electrolyte. Wherein, the porous carbon additive has a BET specific surface area of 100m 2 Porous carbon additives with low specific surface area of less than / g.
2. The positive electrode according to claim 1, in, The BET specific surface area of the porous carbon additive is 70 m 2 / g or less.
3. The positive electrode according to claim 1, in, The particle size D50 of the porous carbon additive is 1.0 μm to 4.0 μm.
4. The positive electrode according to claim 1, in, The bulk density of the porous carbon additive is greater than 0.18 g / cc.
5. The positive electrode according to claim 1, in, The powder resistivity of the porous carbon additive is 0.05 ohm·cm or less.
6. The positive electrode according to claim 1, in, The particle size D50 of the positive electrode active material is 3.0 μm to 8.0 μm.
7. The positive electrode according to claim 1, in, The particle size D50 of the sulfide-based solid electrolyte is 0.1 μm to 1.5 μm.
8. The positive electrode according to claim 1, in, The positive electrode is in the form of a compressed sheet including a positive electrode active material, a sulfide-based solid electrolyte, a conductive material and a porous carbon additive.
9. The positive electrode according to claim 1, in, The positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on one side of the positive electrode current collector; The positive electrode active material layer comprises a positive electrode active material, a sulfide-based solid electrolyte, a conductive material, a binder and a porous carbon additive.
10. The positive electrode according to claim 9, in, The binder includes one or more selected from the group consisting of polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenol resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride-co-hexafluoropropylene).
11. The positive electrode according to claim 1, in, The conductive material is one or more linear conductive materials selected from the group consisting of carbon nanotubes (CNTs) and carbon nanofibers (CNFs).
12. The positive electrode according to claim 1, in, The porous carbon additive is one or more selected from the group consisting of soft carbon and hard carbon.
13. The positive electrode according to claim 1, in, The porous carbon additive is one or more selected from the group consisting of activated carbon and carbon black.
14. The positive electrode according to claim 1, in, The positive electrode has a porosity of 5 volume % to 19 volume %.
15. The positive electrode according to claim 1, in, The content of the positive electrode active material is 55 wt % to 90 wt % based on the total weight of the positive electrode. Wherein, based on the total weight of the positive electrode, the content of the sulfide solid electrolyte is 10 wt % to 50 wt %, Wherein, based on the total weight of the positive electrode, the content of the conductive material is 0.05 wt % to 10 wt %, Wherein, based on the total weight of the positive electrode, the content of the porous carbon additive is 0.1 wt % to 3 wt %. 16 . An all-solid-state battery comprising the positive electrode according to claim 1 , a negative electrode and a sulfide-based solid electrolyte layer disposed therebetween.
Citation Information
Patent Citations
Method for providing contents trading and device using the same
KR1020230094993A